Determinant Factors Affecting Perceived Barriers in Implementing the Covid-19 Health Protocol in The Community - Hema Dewi Anggraheny; Aisyah Lahdji; Disa Yanuar (Ahmad Dahlan Medical Journal, 2022)
Perceived barriers to the application of health protocols are defined as obstacles that arise in carrying out health protocols. The smaller the obstacles, the more people will implement health protocols. Perceived barriers in carrying out health protocols are influenced by demographic areas, education level, employment status, sources of information, and positive experiences of Covid 19. This study aims to determine the factors that influence the perception of the community’s barrier in carrying out health protocols. This study used an analytic observational method with a cross-sectional design. The study was conducted in Semarang, Central Java Province, Indonesia, in November 2021. The research subjects were taken by consecutive sampling as many as 88 people. Perceived barrier questionnaires were prepared, previously through validity and reliability tests. Test the analysis with Mann Whitney and Chi-Square. The majority of people with low perceived barrier are people who live in urban areas (66,7%), have higher education (76,7%), work (93,3%), receive information related to Covid 19 from social media (46,7%), and have no experience of Covid 19 (63,3%). There was a significant relationship between area of residence (p=0,026), education (p=0,003), employment status (p=0,000), experience (0,003) on the perceived barriers from health protocols. The perception of a small barrier is shown in urban communities, higher education, work status, easy media access, and experience that do not intersect with Covid 19. There will be easier to receive education and implement health protocols.   ABSTRAK Hambatan yang dirasakan dalam penerapan protokol kesehatan didefinisikan sebagai hambatan yang muncul dalam melaksanakan protokol kesehatan. Semakin kecil hambatannya, semakin banyak masyarakat yang menerapkan protokol kesehatan. Hambatan yang dirasakan dalam melaksanakan protokol kesehatan dipengaruhi oleh wilayah demografi, tingkat pendidikan, status pekerjaan, sumber informasi, dan pengalaman positif Covid 19. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi persepsi hambatan masyarakat dalam melaksanakan protokol kesehatan. . Penelitian ini menggunakan metode observasional analitik dengan desain cross sectional. Penelitian dilakukan di Semarang, Provinsi Jawa Tengah, Indonesia, pada bulan November 2021. Subjek penelitian diambil secara consecutive sampling sebanyak 88 orang. Kuesioner hambatan yang dirasakan disiapkan, sebelumnya melalui uji validitas dan reliabilitas. Uji analisis dengan Mann Whitney dan Chi-Square. Mayoritas masyarakat dengan persepsi hambatan rendah adalah masyarakat yang tinggal di perkotaan (66,7%), berpendidikan tinggi (76,7%), bekerja (93,3%), menerima informasi terkait Covid 19 dari media sosial ( 46,7%), dan tidak memiliki pengalaman Covid 19 (63,3%). Ada hubungan yang signifikan antara daerah tempat tinggal (p=0,026), pendidikan (p=0,003), status pekerjaan (p=0,000), pengalaman (0,003) terhadap persepsi hambatan protokol kesehatan. Persepsi hambatan kecil ditunjukkan pada masyarakat perkotaan, pendidikan tinggi, status pekerjaan, akses media yang mudah, dan pengalaman yang tidak bersinggungan dengan Covid 19. Akan lebih mudah menerima pendidikan dan menerapkan protokol kesehatan.   This is an open access article under the CC–BY-SA license.